Ako Ay May Kiki/I Have A Vagina - Oris, Glenda C (Archīum Ateneo, 2020)
Ako ay May Kikì/I Have a Vagina is a two-part book intended for young children, parents and caregivers for children. The first and main part of the book is a short story (with appropriate illustrations) that features a five-year old girl narrating to the readers some of the good toilet and perineal hygiene habits that she learned from her mother, so that genitourinary diseases could be prevented. She also shares with the readers the appropriate Filipino clinical term for vagina, as well as the important notions of privacy, autonomy and personal safety vis-à-vis her private part, for example, she underscores that no one else should be allowed to see and touch her vagina other than her mother and herself. Information provided here, as well as the language (words and structure of phrases) and tone used were validated by consultant pediatrician and social worker, a special editorial board and a group of mothers of young children invited for a focus discussion group. The second part of the book is non-literary and contains straightforward information that serve as guide for children and parents/caregivers in asserting children’s safety and autonomy, and identifying red flags regarding sexual predators or abusers. Information shared here are based on clinical studies on the prevention of sexual abuse of children and on actual cases of sexual abuse in the Philippines, and were validated by experts from the Child Protection Unit - Philippine General Hospital. This part also includes contact information of authorities from whom children and their parents/caregivers can seek help and protection.